Effect of arsenic stress on the intestinal structural integrity and intestinal flora abundance of Cyprinus carpio - Shi, Xiaodan; Xu, Wei; Che, Xinghua; Cui, Jiawen; Shang, Xinchi; Teng, Xiaohua; Jia, Zhiying (Frontiers in Microbiology, 2023)
Aquatic organisms such as fish can accumulate high concentration of arsenic (As), which has toxic effects on fish. However, It is unclear whether intestinal flora are involved in As damage to fish intestinal tissues and what the process may entail. The aim of this study was to investigate the effect of As exposure on intestinal microbiota composition and intestinal structural integrity. Common carps (Cyprinus carpio) were exposed to As (2.83 mg/L) in water for 30 days, and blood, muscles, intestines, and intestine contents were collected. Intestinal pathological sections were observed, and lipopolysaccharide (LPS) level in serum, as well as the levels of As accumulation and tight junction-related factors in intestinal tissues were measured. Gut microbiota was identified using 16S rRNA sequencing. The results showed that the abundance of microbiota decreased, the number of harmful bacteria increased, the number of beneficial bacteria decreased in intestines after As treatment. In our experiment, the top 30 harmful and beneficial bacteria with the highest relative abundance were found. Among the top 30 harmful and beneficial bacteria, As treatment resulted in a significant (P < 0.05) increase in harmful bacteria (such as Fusobacteriota, Bacteroidota (LPS-producing bacteria), Verrucomicrobiota, Bacteroides, Aeromonas, and Stenotrophomonas) and a significant (P < 0.05) decrease in beneficial bacteria (such as Actinobacteriota, Planctomycetota, Firmicutes, Reyranella, Akkermansia, and Pseudorhodobacter), further demonstrating that As affected the abundance of intestinal flora. In addition, after As exposure, LPS increased in serum and Bacteroidota (LPS-producing bacteria) in intestine contents. Bacteroidota belongs to the six largest relative abundance flora at phylum level, meaning that LPS produced by Bacteroidota can increase LPS in serum. Additionally, protein and gene levels of tight connection markers ZO-1 and ocludin were reduced by As treatment in intestines, which further indicated that impaired structural integrity of intestines occurred under As exposure condition. In conclusion, the results obtained in our experiment indicated that intestine flora, LPS, and tight connection took part in the pathogenesis of impaired structural integrity of common carp intestines during As exposure.